Sero-epidemiological study of zoonotic bacterial abortifacient agents in small ruminants - Zeeshan, Muhammad Abid; Ali, Sarmad; Ahmed, Ishtiaq; Rehman, Aziz ur; Rafique, Muhammad Kamran; Nasir, Amar; Khan, Aman Ullah; Kashif, Muhammad; Mertens-Scholz, Katja; Arshad, Muhammad Imran; Ehtisham-ul-Haque, Syed; Neubauer, Heinrich (Frontiers in Veterinary Science, 2023)
Abortion is one of the leading causes of economic losses in the livestock industry worldwide. Chlamydia abortus, Coxiella burnetii, and Brucella spp. are the leading cause of late fetal loss in small ruminants. This study determined the seroprevalence of these agents in small ruminants in district Jhang. A total of 385 serum samples were taken from the sheep and goats from different flocks with a history of abortion and subjected to i-ELISA. Further, samples were analysed for liver enzymes and total serum protein using a semi-automated chemistry analyzer. The result of indirect commercial ELISA showed 13.0%, 4.2% and 11.2% prevalence for Coxiella burnetii, Chlamydia abortus, and Brucella spp., respectively. Values of different serum parameters (ALT, AST, and total protein) of seropositive animals were also determined. There was a significant rise in AST and ALT values of infected animals (p≤ 0.05). Total protein decreased for all three infections, but a significant drop was noted in Brucella positive sheep serum samples. Various risk factors were studied. Binary logistic regression proved a significant role of ticks for coxiellosis and brucellosis. Age, parity, and species did not impact the prevalence of diseases studied.